2017
DOI: 10.1016/j.ejca.2017.03.031
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and pattern of bone metastases in 1094 patients with advanced breast cancer – Results from the prospective German Tumour Registry Breast Cancer cohort study

Abstract: A high proportion of patients with breast cancer develop bone metastases, yet data on routine treatment with bone-targeted agents (BTA) are rare. We report real-life outcome data of patients with breast cancer metastasised to the bone treated by office-based oncologists in Germany.The ongoing, prospective, multicentre, population-based cohort study Tumour Registry Breast Cancer (TMK) was started in 2007 in 140 centres across Germany. This interim analysis of 1094 patients with bone metastases revealed differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 29 publications
2
25
1
Order By: Relevance
“…The median OS was 30 and 68.2 months from initial diagnosis in the SEER cohort and FUSCC cohort, respectively, which is similar with the survival reported by previous authors 20, 29, 30, 33. We assume that the longer survival in the FUSCC cohort was because the patients in this cohort were much younger and had less extraosseous metastatic sites.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The median OS was 30 and 68.2 months from initial diagnosis in the SEER cohort and FUSCC cohort, respectively, which is similar with the survival reported by previous authors 20, 29, 30, 33. We assume that the longer survival in the FUSCC cohort was because the patients in this cohort were much younger and had less extraosseous metastatic sites.…”
Section: Discussionsupporting
confidence: 89%
“…We also validated the results of survival analysis in another independent cohort from FUSCC. Some studies have evaluated the epidemiology and prognosis of breast cancer patients with bone metastases at the population level, but most of the patients in these studies presented bone metastases after a diagnosis of early‐stage breast cancer 2, 20, 29, 30, 31, 32, 33. However, limited data have been reported in the specific group of patients with bone metastases upon their initial diagnosis of breast cancer 34.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a similar distribution between types of drugs was seen; zoledronic acid and denosumab were used almost equally. 27 Finally, a study conducted in men with prostate cancer and bone metastasis in routine care in the US showed that BMAs were used at slightly higher rates in this population (77% at 1 year), although incidence of treatment interruption (54% at 1 year) and reinitiation (81% at 1 year) were similar. 28 …”
Section: Discussionmentioning
confidence: 95%
“…The use of bisphosphonates and denosumab in clinical practice has been evaluated in several real-world data sets. Data from a German treatment registry showed that most patients (89%) with bone metastases from breast cancer receive treatment in line with guidelines, with bisphosphonates (primarily ZA) or denosumab started a median of 3 weeks after diagnosis of bone metastases [140]. Notably, data from the Adelphi Prostate Cancer and Breast Cancer Disease Specific Programmes showed that patients with breast cancer are more likely to receive bisphosphonate or denosumab treatment than those with prostate cancer [141].…”
Section: Treatment Guidelines and Real-world Treatment Patternsmentioning
confidence: 99%